Microenvironment reconstitution of highly active Ni single atoms on oxygen-incorporated Mo2C for water splitting - Hou, Mengyun; Zheng, Lirong; Zhao, Di; Tan, Xin; Feng, Wuyi; Fu, Jiantao; Wei, Tianxin; Cao, Minhua; Zhang, Jiatao; Chen, Chen (Nature communications, 2024)
The rational design of efficient bifunctional single-atom electrocatalysts for industrial water splitting and the comprehensive understanding of its complex catalytic mechanisms remain challenging. Here, we report a Ni single atoms supported on oxygen-incorporated Mo 2 C via Ni-O-Mo bridge bonds, that gives high oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) bifunctional activity. By ex situ synchrotron X-ray absorption spectroscopy and electron microscopy, we found that after HER, the coordination number and bond lengths of Ni-O and Ni-Mo (Ni-O-Mo) were all altered, yet the Ni species still remain atomically dispersed. In contrast, after OER, the atomically dispersed Ni were agglomerated into very small clusters with new Ni-Ni (Ni-O-Ni) bonds appeared. Combining experimental results and DFT calculations, we infer the oxidation degree of Mo 2 C and the configuration of single-atom Ni are both vital for HER or OER. This study provides both a feasible strategy and model to rational design highly efficient electrocatalysts for water electrolysis. The comprehensive understanding of complex catalytic mechanisms under harsh reaction conditions for efficient bifunctional single-atom electrocatalysts remain challenging. Here the authors found microenvironment reconsitution of highly active Ni single atoms on oxygen-incorporated Mo2C for water splitting.